2019
DOI: 10.1101/722900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fission yeast Pak1 phosphorylates anillin-like Mid1 for spatial control of cytokinesis

Abstract: Magliozzi et al. show that fission yeast cell polarity kinase Pak1 regulates cytokinesis. Through a phosphoproteomic screen and subsequent mutant analysis, their work uncovers direct targets and mechanisms for Pak1 activity during cell division. AbstractProtein kinases direct polarized growth by regulating the cytoskeleton in time and space, and could play similar roles in cell division. We found that the Cdc42-activated polarity kinase Pak1 colocalizes with the assembling contractile actomyosin ring (CAR) and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…The NDR/LATS kinase Orb6 phosphorylates Gef1 and promotes its binding to 14-3-3 protein Rad24, which displaces Gef1 from the cortex, to reduce polarized activation of Cdc42 [61,70]. On the other hand, a recent phosphoproteomic study has identified Scd1 as one of the p21-activated serine/threonine kinase Pak1 targets involved in polarized growth [89]. Scd1 phosphorylation by Pak1 is important for the regulation of its nuclear shuttling [89].…”
Section: Schizosaccharomyces Pombementioning
confidence: 99%
See 4 more Smart Citations
“…The NDR/LATS kinase Orb6 phosphorylates Gef1 and promotes its binding to 14-3-3 protein Rad24, which displaces Gef1 from the cortex, to reduce polarized activation of Cdc42 [61,70]. On the other hand, a recent phosphoproteomic study has identified Scd1 as one of the p21-activated serine/threonine kinase Pak1 targets involved in polarized growth [89]. Scd1 phosphorylation by Pak1 is important for the regulation of its nuclear shuttling [89].…”
Section: Schizosaccharomyces Pombementioning
confidence: 99%
“…On the other hand, a recent phosphoproteomic study has identified Scd1 as one of the p21-activated serine/threonine kinase Pak1 targets involved in polarized growth [89]. Scd1 phosphorylation by Pak1 is important for the regulation of its nuclear shuttling [89]. In S. cerevisiae, it has already been described that the inhibitory phosphorylation of Cdc24 by PAKs is important in the negative feedback regulation of Cdc42 activity [143,148].…”
Section: Schizosaccharomyces Pombementioning
confidence: 99%
See 3 more Smart Citations